Analysis of National Drug Master Data Characteristics in Supporting Pharmaceutical Management through the Pharmaceutical Information System in Indonesia, 2020–2025 - Isma Oktadiana (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2026)
Digital health transformation requires accurate, complete, and standardized data to support information-based pharmaceutical management. The National Drug Master Data serves as a primary reference to maintain consistent drug information across pharmaceutical information systems. This study aimed to analyze the characteristics of the National Drug Master Data in supporting pharmaceutical information systems in Indonesia during 2020–2025. A quantitative descriptive design was applied using secondary data obtained from the E-Logistics Data Bank of the Ministry of Health of the Republic of Indonesia. A total of 470 drug records were analyzed using descriptive statistics based on object categories, administrative status, data creator organizations, update patterns, and attribute completeness. The results showed that 89.57% of records were categorized as Approved, with drug objects representing the largest proportion (70.43%). Primary identification attributes achieved 100% completeness, while generic name, drug category, and creator organization attributes reached 30%, 52.13%, and 78.72%, respectively. These findings indicate that the National Drug Master Data has a strong structural foundation but requires improvement in attribute completeness, metadata standardization, and data governance to enhance interoperability of national pharmaceutical information systems.